Wifi Security at Edu Hub - Zamros, Nur Amalia; Azlina Bahari (Progress in Engineering Application and Technology, 2022)
Many people can use Wi-Fi without a password or permission in today’s world of globalization and modernity. This is due to the widespread use of open Wi-Fi in public places such as universities, businesses and more. The objective of this project is to give limited time for limited UTHM’s students from streaming YouTube when accessing the Wi-Fi, to avoid hacker or anyone else using Wi-Fi without permission and to allow students make a connection via the internet with secure. The scopes are to limited time UTHM’s students from streaming YouTube when they are using Wi-Fi connection by setting up a firewall to block it. Second, to avoid hackers or anyone else using Wi-Fi without permission by setting each user who wants to use Wi-Fi must have the Wi-Fi password and to allow UTHM’s students to make a connection via the internet securely by setting the network protocol of Virtual Private Network (VPN). The material that was used to complete this project is the MikroTik router by setting up the security using Winbox software. In a nutshell, this project will cover setting Wi-Fi, setting Point-to-Point Tunneling protocol (PPTP) and YouTube blocking settings.